Modern community care: what do we know that is effective? - Burns, T (2009)
Community care has been seen a remarkable expansion in research in the last thirty years. Such research is beset with difficulties including fixing models long enough to get clear comparisons, the absence of consistency in description (particularly of comparator services) and the inevitable contamination from the ‘Pioneer’ effect of highly motivated teams. Assertive Community Treatment (ACT) teams are the most intensively researched but the evidence is contradictory. ACT is a complex intervention and a meta‑regression analysis is reported here that distinguished between the studies in terms of their component parts to identify effective and redundant ingredients. This analysis clarified the overwhelming impact of variation in comparator services. It also confirmed that the core ingredients in traditional generic CMHTs (multidisciplinary working, home‑based care and combined health and social care) ensured an equally effective outcome to the more intensively staffed and carefully prescribed ACT teams. Community mental health services need not follow one prescriptive model. Developing local services should be guided by the research into how effective aspects of care can be incorporated into locally meaningful structures rather than importing complex systems from other health care cultures